STRATEGIES FOR INTEGRATION OF AGRICULTURAL ENTERPRISES INTO INTERNATIONAL MARKETING NETWORKS FOR PRODUCT SALES (Development Service Industry Management, 2024)
In today’s global market, integrating agricultural enterprises into international marketing networks is not just an advantage; it is essential for sustainable growth and competitiveness. Several strategic approaches can be applied to achieve such integration effectively, each tailored to address the unique challenges and opportunities that agricultural producers face. Integrating agricultural enterprises into international marketing networks requires a multifaceted approach encompassing regulatory awareness, branding, strategic partnerships, leveraging digital technologies, capacity building, and innovation. By implementing these strategies, agricultural producers can strengthen their market presence and contribute to the sustainability and resilience of the global food system. The effective foreign economic activity of Ukrainian agricultural enterprises will strengthen their competitive positions in global markets and optimize the structure of exports and imports. Since agricultural exports are the main direction determining the growth of the country’s agribusiness, special attention should be paid to the development of the export activity of agribusiness enterprises. Along with new opportunities in the conditions of modern challenges for enterprises, there are also corresponding risks of objective assessment of various factors of the internal and external environment of the enterprise, determination of competitive advantages, and identification of potential opportunities and threats by developing and implementing a strategy for the enterprise's entry into foreign markets as a comprehensive plan for achieving the set development goals in the long term, which includes appropriate ways and means. Strategy development is a complex process, and its effectiveness determines the success of the enterprise's entry into foreign markets. Integration of agricultural enterprises into international marketing networks for product sales is critical in increasing their competitiveness and ensuring sustainable development. Effective strategies allow you to adapt to the requirements of the global market, expand export potential, and form a positive image of Ukrainian agricultural products at the international level.
Keywords: export; import; integration; strategy; sales networks; competitiveness; development